PROLIFERATIVE VERRUCOUS LEUKOPLAKIA: A PERSISTENT AND HIGH-RISK ORAL DISORDER (International Journal of Food and Nutritional Sciences, 2020)
Proliferative verrucous leukoplakia (PVL) is a unique form of oral leukoplakia characterized by its tendency to expand and develop new lesions, often displaying a warty surface texture. It is typically diagnosed in individuals from their fifth decade onward and is more prevalent in women. The most commonly affected sites include the gingiva, followed by the buccal mucosa and the lateral border of the tongue. PVL is considered an oral potentially malignant disorder with a significant risk of progressing to malignancy. Given its aggressive nature, general dental practitioners (GDPs) must recognize these lesions early to ensure timely referral for further evaluation and diagnosis. Managing PVL remains challenging, requiring long-term monitoring and, when necessary, surgical excision, although recurrence after surgery is common. This article offers an updated review aimed at GDPs, summarizing current knowledge on PVL and discussing management complexities through clinical case examples.